TINGKAT PRODUKTIVITAS PEKERJA PENYUNGKIL KELAPA DENGAN MENGGUNAKAN METODE WORK SAMPLING - Fitri Muhammad Nur; Khairul Ihwan (Program Studi Teknik Industri, 2017)
Work productivity is the ability of employees in production compared with inputs used, an employee can be productive if able to produce goods or services in accordance with the expected in a short time or precise. Productivity is not a quantity calculation, but a ratio, a comparison and is a systematic measurement of an efficiency level. Production is related to quantity, whereas productivity is related to the result of the unity of an input (Sinungan, 1990: 93). Thus the determination of productivity confronted with the desired outcome has been achieved (effectiveness) and the resources used to achieve that result (efficiency). Measurements using measures of efficiency and effectiveness are two dimensions of productivity that are critical in managerial ventures where they can show the productivity index which is the ratio of the extent to which resources are used in conjunction with the achievement of predetermined objectives. The result of the research shows that the productivity level of coconut disguise worker is using work side method for two days, each research for 7 hours is the worker of coconut producer work productively with the result of 95% and the delay ratio equal to 0,07%, and the looseness to the worker The coconut shredding is given is 23.6% with the following details: 12.00% power output, work attitude of 4.5%, work movement of 1.3%, eye fatigue by 0%, working place temperature 5,50%, atmospheric state equal to 0,5%, and good environmental condition equal to 2,50%. Keywords : Work Productivity, Work Sampling